2008
DOI: 10.1523/jneurosci.0136-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Activates the Motor Pattern for Crawling in the Medicinal Leech

Abstract: Locomotion in segmented animals is thought to be based on the coupling of "unit burst generators," but the biological nature of the unit burst generator has been revealed in only a few animal systems. We determined that dopamine (DA), a universal modulator of motor activity, is sufficient to activate fictive crawling in the medicinal leech, and can exert its actions within the smallest division of the animal's CNS, the segmental ganglion. In the entire isolated nerve cord or in the single ganglion, DA induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
120
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(132 citation statements)
references
References 50 publications
11
120
1
Order By: Relevance
“…Parameters and methods used to measure crawl-related burst cycle periods and durations were those of Puhl and Mesce (Puhl and Mesce, 2008;Puhl and Mesce, 2010) and typically involved bursts that had clearly discernable onsets. A minimum of six to 10 consecutive bursts were analyzed for each preparation and means were compared across the number (N) of preparations tested.…”
Section: Statistical Methods and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Parameters and methods used to measure crawl-related burst cycle periods and durations were those of Puhl and Mesce (Puhl and Mesce, 2008;Puhl and Mesce, 2010) and typically involved bursts that had clearly discernable onsets. A minimum of six to 10 consecutive bursts were analyzed for each preparation and means were compared across the number (N) of preparations tested.…”
Section: Statistical Methods and Analysismentioning
confidence: 99%
“…Although DA has been convincingly demonstrated to activate fictive crawling, even in a single ganglion (Puhl and Mesce, 2008), the subcellular and biochemical mechanisms underlying such activation have yet to be explored. To begin to identify these mechanisms, we sought to determine whether crawling-related activity was dependent on cAMP second-messenger signaling.…”
Section: Phosphodiesterase Inhibitors Activate Crawl-like Bursting Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Dopamine, as well as serotonin, is known to play a role in the decision to swim or crawl. In the leech, dopamine has been found to bias behavioral choice toward crawling (Crisp and Mesce, 2004;Puhl and Mesce, 2008), whereas serotonin makes swimming more likely (Friesen and Kristan, 2007). Caenorhabditis elegans also uses dopamine and serotonin to set the balance between these two locomotory behaviors (Vidal-Gadea et al, 2011).…”
Section: Swim Oscillator Interneuronsmentioning
confidence: 99%
“…Neuromodulation, particularly through biogenic amine pathways, has also been a successful research direction in the leech. By adding dopamine and other pharmacological agents to the nervous system through the saline solution, it has been shown that dopamine modulates neural networks involved in decision-making 23 and motor patterns for crawling behavior 24,25 . This experimental approach is a simple (and inexpensive) way to incorporate modulation into the teaching laboratory, and adjusting the ionic makeup of the saline solution is an effective way to teach the Nernst and Goldman-Hodgkin-Katz equations.…”
Section: Discussionmentioning
confidence: 99%